Intersubject differences in the effect of acidosis on phosphocreatine recovery kinetics in muscle after exercise are due to differences in proton efflux rates - van den Broek, Nicole M. A; De Feyter, Henk M. M. L; Graaf, Larry de; Nicolay, Klaas; Prompers, Jeanine J (American Journal of Physiology: Cell Physiology, 2007)
Biomedical NMR, Department of Biomedical Engineering, Eindhoven University of Technology, Eindhoven, The Netherlands Submitted 18 January 2007 ; accepted in final form 21 March 2007 31 P magnetic resonance spectroscopy provides the possibility of obtaining bioenergetic data during skeletal muscle exercise and recovery. The time constant of phosphocreatine (PCr) recovery ( PCr ) has been used as a measure of mitochondrial function. However, cytosolic pH has a strong influence on the kinetics of PCr recovery, and it has been suggested that PCr should be normalized for end-exercise pH. A general correction can only be applied if there are no intersubject differences in the pH dependence of PCr . We investigated the pH dependence of PCr on a subject-by-subject basis. Furthermore, we determined the kinetics of proton efflux at the start of recovery. Intracellular acidosis slowed PCr recovery, and the pH dependence of PCr differed among subjects, ranging from 33.0 to 75.3 s/pH unit. The slope of the relation between PCr and end-exercise pH was positively correlated with both the proton efflux rate and the apparent proton efflux rate constant, indicating that subjects with a smaller pH dependence of PCr have a higher proton efflux rate. Our study implies that simply correcting PCr for end-exercise pH is not adequate, in particular when comparing patients and control subjects, because certain disorders are characterized by altered proton efflux from muscle fibers. 31 P magnetic resonance spectroscopy; skeletal muscle; oxidative capacity; mitochondrial function; intracellular pH Address for reprint requests and other correspondence: J. J. Prompers, Biomedical NMR, Dept. of Biomedical Engineering, Eindhoven Univ. of Technology, N-laag b1.08, PO Box 513, 5600 MB Eindhoven, The Netherlands (e-mail: j.j.prompersattue.nl )